Spatiotemporal Characteristics of Evapotranspiration Paradox and Impact Factors in China in the Period of 1960–2013 - Huiping Huang; Yuping Han; Mingming Cao; Jinxi Song; Heng Xiao; Weili Cheng (Advances in Meteorology)
Downward trend of potential evaporation accompanied with upward of air temperature which is denoted as evaporation paradox has been reported in many regions over the past several decades in the world. In this paper, evaporation paradox and key factors attributed to ET0 changes are systematically analyzed based on data from 599 meteorological stations during 1960–2013. Results show that (1) Evaporation paradox exists in all regions in1960–2013 and 1960–1999 except SWRB in 1960–2013 but no evaporation paradox in 2000–2013. (2) Evaporation paradox exists in large areas in spring and summer, the extent and range fall in autumn, and there is no evaporation paradox in winter. (3) The evaporation paradox area accounts for 73.7% of China in 1960–2013 and 91.2% in 1969–1999. (4) Sunshine hours, humidity, wind speed, and maximum temperature appear to be the most important variables which contributed to ET0 change in China.